Optimal loading conditions for maximizing power in sled resisted sprinting - Cross, M. R.; Brughelli, M.; Samozino, P.; Morin, J.-B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Maximal power production (Pmax) is considered central to sprinting performance (Rabita et al. 2015). Power profiling during sprinting has occurred through several different methods (e.g. Samozino et a. 2015), allowing the magnitude and balance of mechanical capacities to be quantified and compared. However, no attempt has been made to profile the optimal conditions for maximal power during overground sprinting. We assessed whether a multiple trial method, using a common sprint sled to supply resistance, could be used to profile mechanical relationships and optimal loading conditions during overground sprinting. METHODS: 27 healthy mixed-code athletes performed six to seven maximal velocity sprints towing a sled, loaded with a selection of masses (0-120% of bodymass), on an athletics track. For each trial, power was determined at maximum velocity (assessed via radar), from pre-determined friction force and aerodynamic drag. Individual composite linear force-velocity and parabolic power-velocity relationships, and associated mechanical variables and optimal loading conditions, were generated using variables from each trial. Least squares linear and quadratic regression fits, mean and the range of outcome mechanical variables were calculated. RESULTS: Force-velocity and power velocity relationships were very well fitted with linear and 2nd order polynomial regressions, respectively (R2=0.977-0.999; P<0.001). Mean Pmax was 15.79±2.47 W/kg, with theoretical maximum force and velocity as 6.97±0.70 N/kg and 9.13±0.80 m/s, respectively. The mean normal load (i.e. sled mass) that maximized power was 75±7% of body-mass (range=65-90%), representing an optimal force of 3.5±0.34 N/kg at a velocity of 4.58±0.40 m/s. DISCUSSION: Power-force-velocity relationships can be accurately profiled using common sled training equipment and simple maximal speed data. Notably, the optimal conditions for maximizing peak power represented much greater resistance than that generally used in the literature (Petrakos et al. 2015), and appear to exist within wide ranges. This method has potential value in quantifying individualized training parameters for optimized development of horizontal power, which may reflect greater increases in applied performance measures than those currently used and recommended in practice.